Pembelajaran Interaktif Matematika Untuk Taman Kanak-Kanak Berbasis Mobile - Alvius Victor Hartono; Alexander Setiawan; Anita Nathania Purbowo (Jurnal Infra, 2016)
Gadget is an important thing today, childrens already understand how to use gadgets. This makes children spend more time playing gadget than learning. In the world of education, the learning process in children under five is very important. In teaching in kindergarten, children are taught various things, one of which is the introduction of mathematics. Therefore, to improve their interest in learning mathematics, invented an interactive learning app for teaching mathematics kindergarten.The application consists of two menus, namely learning and games. In the learning menu there are four types of learning, recognize numbers, count the objects, mathematical operations, and write numbers. While in the games menu, there were 7 games including counting things, the addition, write numbers, the game sort of numbers, subtracting numbers, fill in the numbers, and comparing numbers. The game of addition and substraction use the accelerometer which allows the user to put ball into hole by moving the device. There is a score in each game. In addition to learning and game menu, the user can change the language used in this game. Available languages are Indonesian, English and Mandarin.Overall, the application can display 5 highest score and able to assist children in learning mathematics. Judging from the results of testing the application which has done to 12 childrens, the child interested in solving problems in the game.